Trends, dynamics and resilience of an Ethiopian wolf population - Marino, J; Sillero-Zubiri, C; Macdonald, D (2006)
Fifteen years of monitoring in the Bale Mountains provide a valuable time series to better understand the dynamics of populations of the endangered Ethiopian wolf Canis simensis in the face of epizootics and increasing human pressure. Linetransect counts in four study areas were used to identify trends in the local abundances of wolves, people, livestock and domestic dogs (a putative rabies reservoir). Estimates of wolf abundance were validated against total counts in prime wolf habitats, where two local populations decimated by rabies in the early 1990s had recovered fully by 2000. Growth appeared to be regulated by negative density dependence, but the rate of growth was unexpectedly low at reduced densities. Limitations to rapid growth, including an initial gap for which data were sparse, are discussed. In a poorer habitat, wolf abundance estimates were less reliable but indicated slight fluctuations without an overall trend. A local extinction was recorded in an area of marginal habitat. With this exception, trends in wolf abundances were unrelated to trends in the abundance of people, livestock or dogs. Rabies emerged as the main cause of decline for high-density populations. The rapidly increasing livestock grazing pressure in Bale gives cause for concern, calling for further research on its impacts upon long-term wolf survival. © 2005 The Zoological Society of London.